Full versus Baby Dose Aspirin for Antithrombotic Prophylaxis in Free Tissue Transfer: Does Size Matter? - Efstathios Karamanos, MD; Rajaie Hazboun, MD; Noah Saad, MD; Christie Bialowas, MD; Howard Wang, MD; Douglas Cromack, MD (Plastic and Reconstructive Surgery, Global Open, 2022)
Background:. The postoperative prophylactic use of aspirin is a common practice among plastic surgeons after free tissue transfer. The use of baby aspirin (81 mg) has become more popular due to previously published literature in other fields. We hypothesized that a full dose daily aspirin is nonsuperior to a baby dose daily aspirin in preventing arterial thrombosis in free tissue transfer. Methods:. All patients undergoing free tissue transfer of the extremities from 2008 to 2020 were retrospectively reviewed. They were divided into two groups based on the postoperative dose of aspirin administered (full versus baby dose). The decision to administer full or baby dose was based on the surgeon’s preference. Primary outcome was revision of the arterial anastomosis. Secondary outcomes included flap complications. Results:. A total of 183 patients were identified. Out of those, 78 patients received full dose aspirin postoperatively, whereas 105 received a baby dose of aspirin. Patients who received baby aspirin did not have a higher incidence of returning to the operating room for revision of their arterial anastomosis [7.6% versus 7.7%; adjusted odds ratio, 0.93 (95% confidence interval, 0.28‐3.11); adjusted P, 0.906]. No differences were found between the two groups in complete and partial flap loss, wound dehiscence, or infection. None of the patients experienced any aspirin-related gastrointestinal complications. Conclusions:. In patients undergoing free tissue transfer, thrombosis of the arterial anastomosis is rare. Administration of a full dose of aspirin postoperatively was not superior to a baby dose of aspirin in preventing arterial-related complications.